Participatory arts in care settings: a multiple case study: innovative practice - Broome, Emma; Dening, Tom; Schneider, Justine M. (SAGE, 2018)
This paper describes two case studies of arts interventions in UK care settings. Visual arts and dance movement interventions were regularly held in two settings. This paper draws on data from qualitative interviews, reflective diary sheets and narrative monitoring reports to examine the content, context, and process of the arts interventions within the care settings. Activity coordinators play a crucial role in the success of arts interventions in care setting through their knowledge and support of residents. We recommend that preparatory consultations should take place between arts practitioners and care personnel, as this seems to improve participation and overall satisfaction.